2009
DOI: 10.1007/s10455-009-9156-x
|View full text |Cite
|
Sign up to set email alerts
|

Gluing constructions amongst constant mean curvature hypersurfaces in $${\mathbb {S}^{n+1}}$$

Abstract: Four constructions of constant mean curvature (CMC) hypersurfaces in S n+1 are given, which should be considered analogues of 'classical' constructions that are possible for CMC hypersurfaces in Euclidean space. First, Delaunay-like hypersurfaces, consisting roughly of a chain of hyperspheres winding multiple times around an equator, are shown to exist for all the values of the mean curvature. Second, a hypersurface is constructed which consists of two chains of spheres winding around a pair of orthogonal equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(38 citation statements)
references
References 25 publications
(98 reference statements)
2
36
0
Order By: Relevance
“…Suppose that balancing condition (2) holds and also that the mapping between finitedimensional vector spaces which takes small displacements of the geodesics forming # ,τ to the quantity given by the left hand side of (2) has full rank. If τ is sufficiently small, theñ ,τ can be perturbed into an exactly CMC hypersurface ,τ .…”
Section: Statement Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Suppose that balancing condition (2) holds and also that the mapping between finitedimensional vector spaces which takes small displacements of the geodesics forming # ,τ to the quantity given by the left hand side of (2) has full rank. If τ is sufficiently small, theñ ,τ can be perturbed into an exactly CMC hypersurface ,τ .…”
Section: Statement Of Resultsmentioning
confidence: 99%
“…The proof of this theorem will follow broadly the same lines as Main Theorem 2 in Butscher's paper [2]. That is, it will be shown that the partial differential equation for the graphing function whose solution gives a CMC perturbation of˜ ,τ can be solved up to a error term belonging to a finite dimensional obstruction space spanned by the approximate Jacobi fields of˜ ,τ (as explained more fully in [2] and in the proof below).…”
Section: Statement Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations